Relationship marketing. Practicum - Raiko, Diana (Tritoria, 2025)
The Practicum consist of the educational and methodological materials for studying the discipline "Relationship Marketing". The block of educational and methodological support includes methodical advice for each topic of the discipline: necessary explanations for the topic, plan of the seminar session, main questions for discussion, practical tasks, tasks for testing knowledge and control questions. Intended for applicants of specialty 075 "Marketing" of all forms of education.
Keywords: tutorial; practicum; relationship marketing; marketing; marketing activities; marketing relations